RESEARCH AND SYNTHESIS OF THE MODAL REGULATOR OF THE TWO-MASS ELECTROMECHANICAL SYSTEM OF THE CRANE LIFTING MECHANISM - N. A. Malev; O. V. Pogoditsky (Известия высших учебных заведений: Проблемы энергетики, 2018)
Research of operation electromechanical system with considering resilient liaison is an actual task. Resilient interactions between the engine and the mechanism increase the load on the mechanical transmission and working equipment and accelerate their wear, increasing degrees of freedom of the system and exciting resonance oscillations. The synthesis of a modal regulator shown that provides an aperiodic transient process. The advantages and disadvantages of this analyzed method.